Reorientasi Koperasi Syariah: Transformasi dari Formalitas Akad menuju Esensi Keadilan Ekonomi - Asep Koswara (LPPM Universitas Koperasi Indonesia, 2026)
This study examines the reorientation of Islamic cooperatives in Indonesia from a formalistic compliance with sharia contracts toward a substantive realization of economic justice. Despite the rapid growth of Islamic cooperative institutions, many of them operate in ways that closely resemble conventional financial intermediaries, emphasizing fixed returns and risk avoidance rather than partnership, empowerment, and wealth redistribution. This condition weakens the transformative role of Islamic cooperatives as instruments of socio-economic justice. Using a qualitative and conceptual research design, this study employs literature-based analysis and analytical synthesis of contemporary Islamic economics and cooperative theory to construct a normative and institutional framework. The study integrates maqasid al-shariah, cooperative principles, and Islamic microfinance perspectives to identify structural inconsistencies between current practices and the ethical foundations of Islamic economics. The main outcome of this research is the formulation of the Islamic Cooperative Justice-Based Model (KS-KKE), which consists of four pillars: maqasid orientation, participatory financing, fair value distribution, and member empowerment. This model shifts the paradigm from contract-centered governance toward justice-centered institutional design. The study concludes that the sustainability and legitimacy of Islamic cooperatives depend not on contractual formalism but on their ability to promote inclusive growth, equitable wealth distribution, and economic empowerment of members.